The Izhma Komi and the Pomor: Two Models of Cultural Transformation - Yuri Shabaev; Valery Sharapov (Journal of Ethnology and Folkloristics)
The article analyses Pomor and Izhma Komi identities. The Pomor and Izhma Komi, who live in the European north of Russia, practically lost their identity during the 20th century and are currently undergoing a process of re-identification. The authors delve into the reasons and circumstances stimulating this process of re-identification, analyse which social groups are the initiators of this process and what is the content of Pomorian and Izhma identity today.